Genetic and biochemical strategies for regulation of L-ascorbic acid biosynthesis in plants through the L-galactose pathway - Castro, Juan C.; Castro, Carlos G.; Cobos, Marianela (Frontiers in Plant Science, 2023)
Vitamin C (L-ascorbic acid, AsA) is a key biochemical micronutrient present in most life forms we know due to its essential and pleiotropic functions in these organisms. Due to its multifunctional role in the human body, since its isolation and molecular structure determination in the last century, it has attracted the attention of the scientific community, which has allowed further studies to elucidate the metabolic pathways for its biosynthesis and degradation in plants, as well as the genetic and biochemical strategies employed by the plant cells for regulating its levels. The construction of this basic knowledge is helping to establish the foundations for generating genetically improved varieties of fruits and vegetables enriched with AsA, commonly used in animal and human feed. Of the four proposed pathways for AsA biosynthesis in plants, the L-galactose pathway has the most robust genetic and biochemical pieces of evidence. The regulation of this biosynthetic pathway at the genetic level occurs in different steps of the genetic information flow (i.e., transcriptional, post-transcriptional, translational, and post-translational levels). Also, at the biochemical level, the regulation depends on the intracellular compartmentalization of its enzymes, the feedback inhibition of allosteric enzymes, metabolon assembly/disassembly, and the enzyme kinetic parameters. In this review, we analyze, in light of discoveries of the last quarter of a century, the genetic and biochemical strategies employed by plant cells for regulating AsA biosynthesis through the L-galactose pathway